2011
DOI: 10.3201/eid1710.110069
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficileInfection in Outpatients, Maryland and Connecticut, USA, 2002–2007

Abstract: Clostridium difficile, the most commonly recognized diarrheagenic pathogen among hospitalized persons, can cause outpatient diarrhea. Of 1,091 outpatients with diarrhea, we found 43 (3.9%) who were positive for C. difficile toxin. Only 7 had no recognized risk factors, and 3 had neither risk factors nor co-infection with another enteric pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…One‐quarter of them had no underlying illness or hospitalization in the preceding year [19]. Similar results were seen in four other studies, where 16%, 26%, 35% and 40% had no antibiotic use or admission preceding their CA‐CDI [22,26,31,32]. Furthermore, severe CDI was reported among previously low‐risk populations, such as healthy individuals and pregnant women [4].…”
Section: Patient and Strain Characteristics In Ca‐cdisupporting
confidence: 76%
See 2 more Smart Citations
“…One‐quarter of them had no underlying illness or hospitalization in the preceding year [19]. Similar results were seen in four other studies, where 16%, 26%, 35% and 40% had no antibiotic use or admission preceding their CA‐CDI [22,26,31,32]. Furthermore, severe CDI was reported among previously low‐risk populations, such as healthy individuals and pregnant women [4].…”
Section: Patient and Strain Characteristics In Ca‐cdisupporting
confidence: 76%
“…When the number of people serviced by a laboratory or hospital (catchment area) is unknown, incidences cannot be determined, and only the percentage of positive tests can be reported. Patients presenting to the GP with diarrhoea have a positive test result for CDI in 2–6% of cases [9,17,23–26]. This increases to c. 10% when antibiotics are used or a physician specifically requests testing, often because risk factors are present [23,27].…”
Section: Occurrence Of CDI In the Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study of the prevalence of CDI among community-dwellers testing positive for CDI in the evaluation of acute diarrheal syndromes showed that 43 of 1091 (3.9 %) such patients tested positive for C. difficile , but only 3 patients (0.3%) remained as possible CDI patients when more recognized causes of outpatient gastroenteritis such as norovirus were excluded. 98 CDI remains extremely unlikely as a cause of outpatient gastroenteritis based on available evidence.…”
Section: Epidemiology Of CDImentioning
confidence: 99%
“…Landmark events contributed to boost the interest on CDI from the medical community over the last 10 years, including: i) hospital outbreaks of unusually severe and recurrent CDI, beginning in the second half of 2002 and extending through 2006 in Québec, Canada(3); ii) dissemination of the strain responsible for this outbreak, now commonly designated 'NAP1/BI/027', in the USA and in Europe (4, 5); iii) emerging reports suggesting that CDI is also significantly encountered in patients who would be erroneously considered without risk, such as community-acquired CDI in patients with no recent antibiotic use (6)(7)(8), or CDI during pregnancy(9); iv) the development and the diversification of diagnostic tests, in-house or commercial, much faster than the pace of recommendations available to guide their use in routine practice (10,11).…”
Section: Introductionmentioning
confidence: 99%